Circulating Ceramide: A New Cardiometabolic Biomarker in Patients With Comorbid Acute Coronary Syndrome and Type 2 Diabetes Mellitus - Cao, Ruihua; Fang, Zhiyi; Li, Sulei; Xu, Mengqi; Zhang, Jibin; Han, Dong; Hu, Wenchao; Yan, Liqiu; Wang, Yabin; Fan, Li; Cao, Feng (Frontiers in Physiology, 2020)
Aims: This study investigated the association of circulating ceramides in comorbidity patients with acute coronary syndrome and type 2 diabetes mellitus (ACS-DM). Methods: 761 patients with coronary heart disease from March to August 2018 admitted to the Cardiology department of Chinese PLA General Hospital were enrolled the study cohort. There were 282 patients diagnosed as acute coronary syndrome (ACS). We selected 65 patients with ACS-DM (ACS-DM group; mean age 64.88 years; 38 men) and 65 non-comorbidity patients only with acute coronary syndrome (ACS group; mean age 64.68 years; 38 men) matched by age and sex. We determined 4 circulating ceramides in 130 plasma samples, which were Cer (d18:1/16:0), Cer (d18:1/18:0), Cer (d18:1/24:1) and Cer (d18:1/24:0). The ceramides in ACS patients and ACS-DM patients were compared. Pearson correlation coefficients between individual ceramides and traditional cardiovascular risk factors for the whole study population were calculated. Multiple logistic regression models were used to evaluate the relativity between the ceramide and ACS-DM. Results: Compared with ACS groups, levels of Cer(d18:1/16:0), Cer(d18:1/18:0), Cer(d18:1/24:1) and their ratios to Cer(d18:1/24:0) were higher in ACS-DM group, and Cer (d18:1/24:0) was lower in ACS-DM group (P < 0.05). Correlation analysis demonstrated mild-to-moderate correlations of ceramide and traditional cardiovascular risk factors. There were relatively strong correlations of Cer(d18:1/18:0), Cer(d18:1/24:1) with C-reactive protein, blood lipids, fasting blood glucose and glycated hemoglobin A1c. In multiple logistic regression models, Cer(d18:1/18:0) (OR: 2.396; 95%CI: 1.103–5.205; P = 0.027), Cer(d18:1/24:1) (OR: 2.826; 95%CI: 1.158-6.896; P = 0.023), Cer(d18:1/18:0)/Cer(d18:1/24:0) (OR: 2.242; 95%CI: 1.103-4.555; P = 0.026) and Cer(d18:1/24:1)/ Cer(d18:1/24:0) (OR: 2.673; 95%CI: 1.225-5.836; P = 0.014) were positively correlated with ACS-DM, and Cer(d18:1/24:0) (OR: 0.200; 95%CI: 0.051-0.778; P = 0.020) was negatively correlated with ACS-DM. Conclusions: Circulating ceramides are positively correlated with the risk of ACS-DM comorbidity. These results demonstrated a new insight to the pathogenesis of the comorbidity of acute coronary syndrome with diabetes, and could provide new options for risk estimation.